INFLUENCE OF LEVEL FERMENTATION OF BASE WINE IN SOME VOLATILE COMPOUNDS OF PERUVIAN ITALIA GRAPE PISCO - Hidalgo, Yasser (2016)
The influence of level fermentation of base wine in some volatile compounds in Pisco obtained therefrom were studied, such as: acetic acid, higher alcohols, esters, acetaldehyde and methanol. In order to evaluate the effect of level fermentation, during this stage five base wine samples with five different cut densities were obtained; to be distilled straight away. The results indicated that piscos obtained from musts with lower fermentation levels, expressed by higher cut densities (990; 1,000; 1,010; 1,025 and 1,040 g/L), show higher acetic acid (0.15, 0.16, 0.17, 0.17 and 0.18 g/L), propanol (72.15, 76.33, 82.25, 89.86 and 95.50 mg/100 mL anhydrous alcohol), ethyl acetate (22.00, 30.72, 34.26, 39.06 and 49.68 mg/100 mL anhydrous alcohol), acetaldehyde (22.71, 40.52, 48.69, 58.51 y 78.62 mg/100 mL anhydrous alcohol) and methanol (39.22, 40.27, 43.33, 51.30 and 57.95 mg/100 mL anhydrous alcohol) contents; and lower iso/ter-amyl alcohol (122.83, 118.98, 115.78, 102.88 and 100.11 mg/100 mL anhydrous alcohol).contents.